Police-Youth Programs as Citizen-State Interactions: A Case Study of Police and Underrepresented Youth Perceptions - Vernise Estorcien; Andrea M. Headley (Journal of Social Equity and Public Administration, 2025)
Interactions with government impact the perceptions and experiences of underrepresented and marginalized groups. Public agencies are increasingly implementing programs designed explicitly for underrepresented citizens to improve these interactions. In the United States, the Miami-Dade County, Florida police-youth program aims to promote positive perceptions and experiences for underrepresented and marginalized youth through citizen-state interactions. This case study qualitatively examined the features and impact of a police-youth program using virtual semi-structured interviews with police officers and youth. The findings revealed that building trusting relationships between the police and marginalized youth requires an understanding of the contexts marginalized youth are embedded in, as well as informal and positive interactions. Despite the program’s best efforts, negative perceptions of the police are common among marginalized youth and are influenced by media, history, and personal or vicarious police encounters. Thus, efforts to improve perceptions may take time and persistence.